Internal conflict, market uniformity, and transparency in price competition between teams - Michael Kurschilgen; Alexander Morell; Ori Weisel (Max Planck Institute for Research on Collective Goods, 2016)
The way profits are divided within successful teams imposes different degrees of internal conflict. We experimentally examine how the level of internal conflict, and whether such conflict is transparent to other teams, affects teams' ability to compete vis-à-vis each other, and, consequently, market outcomes. Participants took part in a repeated Bertrand duopoly game between three-player teams which had either the same or different level of internal conflict (uniform vs. mixed). Profit division was either private-pay (high conflict; each member received her own asking price) or equal-pay (low conflict; profits were divided equally). We find that internal conflict leads to (tacit) coordination on high prices in uniform private-pay duopolies, but places private-pay teams at a competitive disadvantage in mixed duopolies. Competition is softened by transparency in uniform markets, but intensified in mixed markets. We propose an explanation of the results and discuss implications for managers and policy makers.
Keywords: D43; L22; C92; 330; Organizations; Conflict; Sharing Rules; Competition; Heterogeneity; Transparency; Experiment